Handshake, No. 11 (October 2013) - International Finance Corporation (International Finance Corporation, Washington, DC, 2015)
This issue includes the following headings: donors: aid versus trade; investment: seeking strong partners; power: hydro heats up; water: sanitation solutions; and first person: African Development Bank President